Phage Lytic Protein LysRODI Prevents Staphylococcal Mastitis in Mice - Gutiérrez, Diana; Garrido, Victoria; Fernández, Lucía; Portilla, Silvia; Rodríguez, Ana; Grilló, María Jesús; García, Pilar (Frontiers in Microbiology, 2020)
Phage lytic proteins are promising antimicrobials that could complement conventional antibiotics and help to combat multi-drug resistant bacteria that cause important human and animal infections. Here, we report the characterization of endolysin LysRODI (encoded by staphylophage phiIPLA-RODI) and its application as a prophylactic mastitis treatment. The main properties of LysRODI were compared with those of endolysin LysA72 (encoded by staphylophage phiIPLA35) and the chimeric protein CHAPSH3b (derived from the virion-associated peptidoglycan hydrolase HydH5 and lysostaphin). Time-kill experiments performed with Staphylococcus aureus and Staphylococcus epidermidis demonstrated that the killing rate of LysRODI and CHAPSH3b is higher than that of LysA72 (0.1 µM protein removed 107 CFU/ml of S. aureus in 30 min). Of note, all proteins failed to select resistant mutants as bacterial exposure to sub-lethal concentrations of the proteins did not alter the MIC values. Additionally, LysRODI and CHAPSH3b were non-toxic in a zebrafish embryo model at concentrations near the MIC (0.5 and 0.7 µM, respectively). Moreover, these two proteins significantly reduced mortality in a zebrafish model of systemic infection. In contrast to LysRODI, the efficacy of CHAPSH3b was dose-dependent in zebrafish, requiring higher-dose treatments to achieve the maximum survival rate. For this reason, LysRODI was selected for further analysis in mice, demonstrating great efficacy to prevent mammary infections by S. aureus and S. epidermidis. Our findings strongly support the use of phage lytic proteins as a new strategy to prevent staphylococcal mastitis.